Spatial variability of soil erodibility in response to different agricultural land use at highland farms - Nasidi, Nuraddeen M.; Abdullah, Ahmad F.; Shanono, Nura J.; Wayayok, Aimrun; M. Kassim, Muhamad S. (College of Agriculture, University of Basrah, 2021)
This work describes the effect of different agricultural land use on potential soil erodibility (K) at cultivated farming areas in Cameron Highlands. Ordinarily, soils are assigned with K factors depending on geological properties only which can result into erroneous calculation of soil erosion. This study explores roles of different agricultural land use on the spatial variability of soil erodibility on hilly farms at Cameron Highlands. Soil samples, slopes and spatial locations were collected based on crop types being cultivated. Meanwhile, the land use and type of equipment for each crop are recorded and ranked depending on the degree of soil disturbances. The results showed that, K values are ranged from 0.0084 to 0.0161. Shallow-root crops, such as vegetables and flowers have higher K values due to shallow soil rootzone and frequency of surface operations. However, tea cultivated areas and forests have low K values, indicating comparably higher ability to resist erosion. Furthermore, the erodibility factor for tea farms shows increasing patterns along the developmental stages while the reverse was found in vegetable farms. Spatial variability of the K is influenced by various farming operations at different growing stages and the peculiarity of each crop. This work demonstrated that, the soil erodibility factor can be determined considering the crops and stages of development, in addition to geological attributes.